Keanekaragaman Jenis Burung di Berbagai Tipe Habitat di Kawasan Ekonomi Khusus (KEK) Likupang, Sulawesi Utara - Migael, Migael; Langi, Martina Agustina; Nurmawan, Wawan (Silvarum, 2025)
This study examined bird species diversity in various habitat types in Likupang SEZ, North Sulawesi. Using the point count method, this study found 69 bird species from 35 families and 3 bird species from 2 families found outside the location and observation hours. Five bird species with the highest Index of Importance (INP) were Aerodramus vanikorensis, Collocalia esculenta, Corvus celebensis, Geopelia striata, and Pycnonotus aurigaster. Secondary forest had the highest bird species diversity with a diversity index of 2.99, followed by open hills H' (2.86) and coastline H' (2.48). There are 44 bird species that have the potential for birdwaching ecotourism by considering the attractiveness of morphological uniqueness (feather and beak color), sound, migratory birds, endemic and protected status. Keywords: Bird Species Diversity, Habitat Type, Birdwatching, Likupang SEZ